Evaluation of stable isotope ratios of historical and modern samples of invasive and indigenous murid rodents, with respect to historical urbanization in Gauteng Province, South Africa - Chimimba, Christian Timothy (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2024.